Corporate blogging e motivazione del personale. Paradigmi e prospettive verso un sistema di CRM per la valutazione dell’engagement dei dipendenti - Claudia Bernardo (Culture e Studi del Sociale)
Starting from the assumption that motivation moves people and people move the business through their performances, this work aims to offer a preliminary examination of the blogging phenomenon, then it focuses on corporate blogging as a tool to generate staff motivation and feed Customer Relationship Management (CRM) internal programs for the employees. The well-known familiarity with the digital conversations, offered by the web, seems a good prerequisite for not excluding blogging from the opportunities for conversation with the public inside the organization, using it as a stimulus for the satisfaction and care of the employee. Along this way new possible multidisciplinary research paths open up.